2023
DOI: 10.1021/acs.inorgchem.2c04196
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Cyclohexane to Cyclohexanol/Cyclohexanone by Surface Peroxo Species on Cu-Mesoporous TiO2

Abstract: Selective oxidation of cyclohexane to cyclohexanol/ cyclohexanone (KA−oil) is an important chemical process, which is still constrained by low conversion and selectivity and high energy consumption. In this study, Cu-doped mesoporous TiO 2 (Cu-MT) has been successfully synthesized via calcinating MIL-125(Ti) doped with copper acetylacetonate, which shows high reactivity in selective oxidation of cyclohexane to KA−oil by persulfate (PS) with the desirable cyclohexane conversion of 16.8% and a selectivity of 98.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, considering that MeOH is an effective scavenger for both ⋅ OH and SO 4 ⋅ − , it can also be ruled out given it was the solvent used in this study [20] . Our recent works revealed that PS could be effectively activated via the non‐radical pathway on CuO or Cu‐doped mesoporous TiO 2 under alkaline conditions [12,13a] . To further investigate where the hydrogen of the N−H bond in the reaction, CH 3 OD was used to replace MeOH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, considering that MeOH is an effective scavenger for both ⋅ OH and SO 4 ⋅ − , it can also be ruled out given it was the solvent used in this study [20] . Our recent works revealed that PS could be effectively activated via the non‐radical pathway on CuO or Cu‐doped mesoporous TiO 2 under alkaline conditions [12,13a] . To further investigate where the hydrogen of the N−H bond in the reaction, CH 3 OD was used to replace MeOH.…”
Section: Resultsmentioning
confidence: 99%
“…Oxone was proved to be the best choice, and there was no 3 a generation without the addition of oxidants (entry 11), indicating direct oxidation by air is negligible. In addition, different additives exhibited various yields (0-57 %, entries [12][13][14][15][16][17], and the yield was only 3 % (entry 18) in the absence of additives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxidizing species on the surface of catalysts (e.g., superoxo and peroxo species) can effectively mediate the oxidation selectivity of H-rich substrates via the H-abstraction pathway. , For instance, our recent works suggested that the surface Bi–OO• superoxo and Bi–OOH peroxo during the photocatalytic activation of O 2 on Bi 2.15 WO 6 not only selectively oxidized benzyl alcohol to benzaldehyde via the H-abstraction pathway, but also contributed to the oxidation of various H-donors such as As­(III), glucose and phenolics with the production of H 2 O 2 , indicating the high reactivity of surface superoxo and peroxo species in H-abstraction . Likewise, Lyu et al suggested that the surface Ti–OOH peroxo on Pd@HTS-1 achieved 46.4% conversion of benzyl alcohol with high selectivity of 100% toward benzaldehyde.…”
Section: Introductionmentioning
confidence: 99%